Analysis of the Retinal Nerve Fiber Layer in Retinitis Pigmentosa Using Optic Coherence Tomography. (16th August 2015) - Yıldırım, Medine Aslı; Erden, Burak; Tetikoğlu, Mehmet; Kuru, Özlem; Elçioğlu, Mustafa
Abstract : Aim . To evaluate the peripapillary retinal nerve fiber layer (RNFL) changes in retinitis pigmentosa (RP) patients using spectral domain optic coherence tomography (Sd-OCT). Methods . We retrospectively examined medical records of forty-four eyes of twenty-two RP patients. The results were also compared with those of previously reported forty-four eyes of twenty-two normal subjects (controls). Records of average and four quadrants peripapillary RNFL thickness measurements using Sd-OCT were assessed. Results . In RP patients the mean RNFL thickness was 97.57 ± 3.21 μ m. The RNFL in the superior, temporal, nasal, and inferior quadrants was 119.18 ± 4.47 μ m, 84.68 ± 2.31 μ m, 75.09 ± 3.34 μ m, and 113.88 ± 4.25 μ m, respectively. While the thinning of RNFL was predominantly observed in the inferior quadrant, the thickening was mostly noted in temporal quadrant. The differences between mean, superior, and nasal quadrant RNFL thicknesses were not statistically significant when compared with control group. The RP patients had thinner inferior quadrant and thicker temporal quadrant than control group (p < 0.05 ). Conclusion . Sd-OCT is highly sensitive and effective instrument to detect RNFL changes in RP patients. RNFL measurements can provide information about the progression of retinitis pigmentosa and may provide prognostic indices for future treatment modalities.